1967
DOI: 10.1042/bj1040353
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of skeletal-muscle fructose 1,6-diphosphatase by adenosine monophosphate

Abstract: 1. The present study extends the finding of Krebs & Woodford (1965) that muscle fructose diphosphatase is more sensitive to AMP inhibition than liver fructose diphosphatase. 2. Hen breast fructose diphosphatase has a K(i) for AMP of 0.1mum; the plot of percentage inhibition is non-sigmoid and the reciprocal plot of activity against AMP concentration is sometimes linear. 3. Percentage inhibition plots for other muscle fructose diphosphatases are sigmoid curves which exhibit different threshold responses to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1967
1967
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 12 publications
2
25
0
Order By: Relevance
“…As shown in Table 1, it was necessary to use the crude extract for assay of PFK activity because the enzyme from some muscles is partially sedimented after centrifugation at 10000g and 114000g (in the ionic extraction medium). The values presented in a preliminary communication (Opie & Newsholme, 1965) were based on assays of the 114 OOOg supernatant, which explains why those activities are much lower than those now reported.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…As shown in Table 1, it was necessary to use the crude extract for assay of PFK activity because the enzyme from some muscles is partially sedimented after centrifugation at 10000g and 114000g (in the ionic extraction medium). The values presented in a preliminary communication (Opie & Newsholme, 1965) were based on assays of the 114 OOOg supernatant, which explains why those activities are much lower than those now reported.…”
Section: Resultsmentioning
confidence: 56%
“…This investigation showed that phosphoenolpyruvate carboxykinase [GTP-oxaloacetate carboxy-lyase (transphosphorylating), EC 4.1.1.32] was present in white muscle, and, moreover, that the variation in its activity between various muscles corresponded to that of FDPase. A preliminary report of some of these results has been published (Opie & Newsholme, 1965 Mansour, 1965). …”
mentioning
confidence: 99%
“…Pyruvate dehydrogenase (PDH) and phosphofructokinase (PFK) activities were measured as described (11,12). ACC and CitLy activities were measured spectrophotometrically as reported previously (13,14).…”
Section: Fatty Acid and Glycogen Synthesis In Bat And Watmentioning
confidence: 99%
“…The enzyme suspensions were centrifuged, the sedimented protein was dissolved in quartzdistilled water, and the solutions were treated with Sephadex G-25 (Pharmacia Fine Chemicals, Uppsala, Sweden). Activity determinations of hexosediphosphatase in crude extracts are complicated by the inhibitory effect of AMP [22,35,36]. I n order to remove AMP from the extracts, various methods were examined, e. g .…”
Section: Enzyme Activity Determinationsmentioning
confidence: 99%